SIRT1-regulated ROS generation activates NMDAR2B phosphorylation to promote central sensitization and allodynia in a male chronic migraine rat model - Zhang, Xiaoyan; Zhang, Wei; Wang, Yanyun; Zhang, Yun; Zhang, Dunke; Qin, Guangcheng; Zhou, Jiying; Chen, Lixue (Frontiers in Molecular Neuroscience, 2024)
Background Central sensitization is one of the pivotal pathological mechanisms in chronic migraine (CM). Silent information regulator 1 (SIRT1) was shown to be involved in CM, but its specific mechanism is unclear. Reactive oxygen species (ROS) are increasingly regarded as important signaling molecules in several models of pain. However, studies about the role of ROS in the central sensitization of CM model are rare. We thus explored the specific process of SIRT1 involvement in the central sensitization of CM, focusing on the ROS pathway. Methods Inflammatory soup was repeatedly administered to male Sprague–Dawley rats to establish a CM model. The SIRT1 expression level in trigeminal nucleus caudalis (TNC) tissues was assessed by qRT–PCR and Western blotting analysis. The levels of ROS were detected by a Tissue Reactive Oxygen Detection Kit, DHE staining, and the fluorescence signal intensity of 8-OHdG. A ROS scavenger (tempol), a SIRT1 activator (SRT1720), a SIRT1 inhibitor (EX527), and a mitochondrial fission inhibitor (Mdivi-1) were used to investigate the specific molecular mechanisms involved. NMDAR2B, CGRP, ERK, and mitochondrial fission-related protein were evaluated by Western blotting, and the CGRP level in frozen sections of the TNC was detected via immunofluorescence staining. Results After repeated inflammatory soup infusion and successful establishment of the CM rat model, SIRT1 expression was found to be significantly reduced, accompanied by elevated ROS levels. Treatment with Tempol, SRT1720, or Mdivi-1 alleviated allodynia and reduced the increase in NMDAR2B phosphorylation and CGRP and ERK phosphorylation in the CM rat. In contrast, EX527 had the opposite effect in CM rat. SRT1720 and EX527 decreased and increased ROS levels, respectively, in CM rats, and tempol reversed the aggravating effect of EX527 in CM rats. Furthermore, the regulatory effect of SIRT1 on ROS may include the involvement of the mitochondrial fission protein DRP1. Conclusion The results indicate the importance of SIRT1 in CM may be due to its role in regulating the production of ROS, which are involved in modulating central sensitization in CM. These findings could lead to new ideas for CM treatment with the use of SIRT1 agonists and antioxidants.